A prospective open-label pilot study of fluvastatin on proinflammatory and prothrombotic biomarkers in antiphospholipid antibody positive patients. Issue 6 (9th August 2013) - Erkan, Doruk; Willis, Rohan; Murthy, Vijaya L; Basra, Gurjot; Vega, JoAnn; Ruiz-Limón, Patricia; Carrera, Ana Laura; Papalardo, Elizabeth; Martínez-Martínez, Laura Aline; González, Emilio B; Pierangeli, Silvia S
Abstract : Objective: To determine if proinflammatory and prothrombotic biomarkers are differentially upregulated in persistently antiphospholipid antibody (aPL)-positive patients, and to examine the effects of fluvastatin on these biomarkers. Methods: Four groups of patients (age 18–65) were recruited: (a) primary antiphospholipid syndrome; (b) systemic lupus erythematosus (SLE) with antiphospholipid syndrome (APS) (SLE/APS); (c) persistent aPL positivity without SLE or APS (Primary aPL); and (d) persistent aPL positivity with SLE but no APS (SLE/aPL). The frequency-matched control group, used for baseline data comparison, was identified from a databank of healthy persons. Patients received fluvastatin 40 mg daily for 3 months. At 3 months, patients stopped the study medication and they were followed for another 3 months. Blood samples for 12 proinflammatory and prothrombotic biomarkers were collected monthly for 6 months. Results: Based on the comparison of the baseline samples of 41 aPL-positive patients with 30 healthy controls, 9/12 (75%) biomarkers (interleukin (IL)-6, IL1β, vascular endothelial growth factor (VEGF), tumour necrosis factor (TNF)-α, interferon (IFN)-α, inducible protein-10 (IP10), soluble CD40 ligand (sCD40L), soluble tissue factor (sTF) and intracellular cellular adhesion molecule (ICAM)-1) were significantly elevated. Twenty-four patients completed the study; fluvastatin significantly and reversibly reduced the levels of 6/12 (50%) biomarkers (IL1β, VEGF, TNFα, IP10, sCD40L and sTF). Conclusions: Our prospective mechanistic study demonstrates that proinflammatory and prothrombotic biomarkers, which are differentially upregulated in persistently aPL-positive patients, can be reversibly reduced by fluvastatin. Thus, statin-induced modulation of the aPL effects on target cells can be a valuable future approach in the management of aPL-positive patients.